A systematic, mixed studies review of the outcomes of community garden participation related to food justice. Issue 1 (2nd January 2021) - Burt, Kate G.; Mayer, Gail; Paul, Rachel
ABSTRACT: Community gardens have been proposed as a way to build community capacity while simultaneously improving equity in food systems, core tenets of the food justice movement. Yet to date, there is no literature that connects the evidence-based outcomes of community gardening with specific social and dietary aspects of the movement. To explore this, we analysed 277 community gardening articles, which resulted in 31 quantitative, qualitative, or mixed methods studies that met the inclusion criteria for this synthesis. An appraisal of the quality of each included study was conducted. Results of the synthesis indicate many positive impacts across seven outcomes: three related to the social benefits of gardening (social capital, neighbourhood participation, community sharing) and four related to the dietary benefits of gardening (fruit and vegetable intake, food quality, food security, access to produce). Findings were similar across studies, although methodological rigour in study design and lack of participant racial/ethnic and socioeconomic diversity were common issues. Studies found that community garden participation is positively correlated with aspects of community connectedness but evidence demonstrating that it improves diet is neutral. Given these results, that community gardening may be an effective strategy to create a more equitable and just food system remains unclear.